Kualitas Kompetensi Guru BK sebagai Konselor di Sekolah - Apri Sara Banjarnahor; Hanifa Raihan Fakhira Purba; Rizka Andriyani; Syakira Nazla Simbolon; Rizky Ananda Syafitri (Universitas Palangka Raya, 2024)
This study aims to analyze efforts or solutions in overcoming the problem of the quality of the competence of guidance and counseling teachers, where many guidance and counseling teachers are found who are not from the BK department. Data was collected through descriptive qualitative methods with interviews and observations at Dharmawangsa High School. The subject of this study is a BK teacher at Dharmawangsa High School. The results of the study showed that there were guidance and counseling teachers who did not come from the BK department, and resulted in less optimal and effective counseling that was running, due to a lack of mastery of the duties of guidance and counseling teachers.